Pemanfaatan Rosin (Gondorukam) - Hayat S (Jurnal Kimia dan Kemasan, 1987)
Rosin is residue from distillation process pine gum, extraction pine stump wood. It was get by product pulp industry form rosin tall oil. Rosin is a complex mixture of mainly resin acids and a small amount of nonacidic component. it can be reacted with metal hydroxide namely calcium hydroxide, zinc hydroxide, aluminium hydroxide and sodium hydroxide.